Application of the Analytical Hierarchy Process (AHP) Method in Determining the Best Employees - Rahal (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2022)
Human resources are the most important part for the growth and development of a company. A company can develop well, of course, it is influenced by the quality of human resources, which in this case are employees who work in the company. Determination of the best employees is done not only by direct appointment by the leader or manager, but a company must conduct a performance assessment that has been carried out by its employees within a certain period of time, and of course there will be a reward for the success that has been achieved by its employees. The decision support system for determining the best employees is carried out using the Analytical Hierarchy Process (AHP) method to determine the weight of each criterion, to rank alternatives in the form of employee data. This research produces a decision support system that can recommend the best employees at PT. Medisafe Technologies based on the criteria that have been set by the AHP method.